Praktik Akad Wadi’ah pada Lahan Parkir Indomaret Fresh Bandorasa Wetan Kecamatan Cilimus Kabupaten Kuningan - Ashari, Azmi Azizah; Mualim, Mualim; Hidayat, Yayat (AL-MASHALIH (Journal of Islamic Law), 2025)
The practice of using a wadi’ah (safekeeping) contract for parking motor vehicles is common in various places, including at Indomaret Fresh Bandorasa Wetan. However, it remains unclear whether the implementation of this wadi’ah contract complies with its pillars (rukun) and conditions as stipulated in Islamic law. This study aims to examine the implementation of the wadi’ah contract in the parking area of Indomaret Fresh Bandorasa Wetan and to assess its conformity with Islamic legal principles. This study used a field research strategy with an emphasis on qualitative data. Observation, interviews, and written records were the means of data collection. The findings reveal that the practice of wadi’ah at the Indomaret Fresh Bandorasa Wetan parking area involves customers entrusting their vehicles to a parking attendant. Initially, there were no attendants, but due to an increase in the number of customers, a parking attendant was later assigned. From an Islamic legal perspective, the wadi’ah contract practice in this setting does not yet fulfill the necessary pillars and conditions. One notable issue is that service users (mudi’) do not receive a parking ticket from the attendant, which is a requirement for clarity and accountability. Additionally, if the item entrusted is one that can be properly safeguarded, any loss of the item obligates compensation.